Antibacterial mechanism of forsythoside A against Pseudomonas syringae pv. actinidiae. (December 2022) - Pei, Hurong; Lu, Mingxiu; Long, Li; Long, Zhangfu
Abstract: In this study, we investigated the antibacterial mechanism of forsythoside A against the kiwifruit canker pathogen, which provided the theoretical basis for the prevention and control of canker disease and the development of plant-based fungicides. The pathogenic bacteria were isolated from kiwifruit diseased tissues and the specific primers Psa_A1 F2 and Psa_A1 R1 were used for preliminary identification. Four pairs of housekeeping genes, including gapA, gltA, gyrB, and rpoD, were used for polygenic typing identification. The inhibition effect of forsythoside A on Psa was evaluated by the filter paper bacteriostasis method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Psa were determined by the 96-well plate absorbance and colony counts. The changes in Psa biofilm formation, motility, IAA synthesis, iron utilization, and respiratory chain dehydrogenase activity were determined. The Psa morphology was observed by Scanning electron microscope (SEM) and transmission electron microscope (TEM). The expression of some virulence genes was analyzed by qPCR. The results showed that the pathogen was Pseudomonas syringae pv. actinidiae (Psa). The inhibitory effect of forsythoside A on Psa was positively correlated with its concentration. while the MIC and MBC were 2.0 and 5.0 mg/mL, respectively. The biofilm formation and motility of Psa were not only obviously inhibited, but also the substance and energy metabolism were interfered, while obvious deformity and rupture of the cells were occurred in Psa Bacteria. In addition, The transcription of the Psa pathogenic genes was affected. The infection investigation of kiwifruit leaves indicated that forsythiaside A inhibits Psa pathogenicity and had a protective effect. This study concluded that forsythoside A has a certain control effect on kiwifruit canker, and has the potentiality to be developed as a novel plant fungicide. Graphical abstract: Image 1 Highlights: The strains were isolated from kiwifruit pathogenic tissues. The isolation strain was identified by amplification of four housekeeping genes. The mechanisms were Investigated for Psa inhibition by forsythoside A. Inhibitory effect of forsythoside A was studied on transcription of virulence genes. The protective effect was studied for forsythoside A on Psa-infected kiwifruit leaves.